2019
DOI: 10.1177/0145561319872166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Smoking on the Auditory System: Is There a Gender Difference?

Abstract: The main aim of our study is to evaluate whether the effect of smoking on the auditory system shows gender differences. Another aim is to evaluate whether smoking has any influence on the absorbance of sound. There were 236 volunteers including 90 nonsmokers (42 females and 48 males) and 146 smokers (72 females and 74 males) in the study. Smokers were grouped according to pack-years of smoking as 5 to 10 pack-years, 11 to 20 pack-years, and more than 20 pack-years. Pure tone audiometry and wideband tympanometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Only 2% of the women in the study (based in China) smoked, however, likely reducing the statistical power to detect significant results in women ( Wang et al 2021 ). In contrast, Demir et al found that hearing loss may occur at lower rates of smoking (measured in lifetime pack-years) in women than in men ( Demir et al 2019 ). The findings of our study are in contrast to a large meta-analysis that demonstrated that the relative risk of current smoking (versus not smoking) on coronary heart disease was 25% higher for women than men ( Huxley & Woodward 2011 ).…”
Section: Discussionmentioning
confidence: 96%
“…Only 2% of the women in the study (based in China) smoked, however, likely reducing the statistical power to detect significant results in women ( Wang et al 2021 ). In contrast, Demir et al found that hearing loss may occur at lower rates of smoking (measured in lifetime pack-years) in women than in men ( Demir et al 2019 ). The findings of our study are in contrast to a large meta-analysis that demonstrated that the relative risk of current smoking (versus not smoking) on coronary heart disease was 25% higher for women than men ( Huxley & Woodward 2011 ).…”
Section: Discussionmentioning
confidence: 96%